Exploring joyful, mindful, and meaningful learning in Surakarta high school Geography education - Albertus Erico Jerry Krisna Nugroho; Sugiyanto Sugiyanto; Singgih Prihadi (Indonesian Journal of Educational Development (IJED), 2026)
Deep learning implementation in Indonesian education has encouraged the development of joyful, mindful, and meaningful learning experiences. However, previous studies have predominantly focused on policy discourse, teacher readiness, and general pedagogical transformation, while limited research has explored how these principles are experienced in geography classrooms from multiple educational perspectives. While previous studies have primarily focused on policy discourse and teacher readiness, limited research has examined how these principles are experienced in geography classrooms from multiple educational perspectives. Therefore, this study aimed to explore the implementation of joyful, mindful, and meaningful learning in geography education from the perspectives of teachers, vice principals for curriculum affairs, and students in public high schools in Surakarta, Indonesia. This study employed a qualitative exploratory design using purposive sampling. Participants included nine geography teachers, nine vice principals for curriculum affairs, and Phase F geography students from nine public high schools. Data were collected through semi-structured interviews and open-ended questionnaires and analyzed using thematic analysis. The findings revealed that joyful learning was reflected through interactive and participatory classroom practices, mindful learning developed through reflective inquiry and critical geographic awareness, and meaningful learning emerged through contextual and authentic learning experiences related to students’ real-life environments. The study also found that these three principles were interconnected in supporting deeper and more student-centered geography learning. This study contributes to geography pedagogy by providing a multi-perspective understanding of deep learning implementation within the Merdeka Curriculum context in Indonesia. The findings offer practical insights for geography teachers and school leaders in designing more engaging, reflective, and contextually relevant learning experiences.